Design and optimization of process parameters of polyvinyl (alcohol)/chitosan/nano zinc oxide hydrogels as wound healing materials. (1st March 2019) - Khorasani, Mohammad Taghi; Joorabloo, Alireza; Adeli, Hassan; Mansoori-Moghadam, Zohreh; Moghaddam, Armaghan
Highlights: Bionanocomposite based hydrogels were formed using freeze-thaw method. RSM was used for evaluation of important process parameters. Processing parameters of prepared hydrogels were successfully optimized using RSM. Hydrogel wound dressings had proper mechanical properties in dry and wet states. Hydrogels are significantly able to protect the wounds against microorganisms. Abstract: Composite hydrogels as wound dressings feature healing properties in treating wounds. In this study, polyvinyl (alcohol)/chitosan/nano zinc oxide nanocomposite hydrogels were formed using the freeze-thaw method and essential process parameters including thawing time, thawing temperature, and the number of freeze-thaw cycles was investigated to model nanocomposites employing response surface methodology. Critical properties including water vapor transmission rate, porosity, wound fluid absorption, and gel content were modeled using process parameters. Analysis of morphology, mechanical properties, toxicity, protein absorption, antibacterial activity, and in-vitro wound healing were also performed. Results exhibited that increased freeze-thaw cycles caused reduced pore size and increased porosity and wound fluid absorption. Besides, increased freeze-thaw cycles and reduced thawing temperature resulted in increased elastic modulus and tensile strength, while elongation at break point decreased. Antibacterial properties, biocompatibility, and in-vitro wound healing tests demonstrated that the designed system showed no toxicity and it was able to treat the wounds sufficiently.